A importância das forças armadas para o desenvolvimento tecnológico do Brasil (2008-2018) - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Relationships between university, business and government have been of relevance in the scientific and business context, generating the improvement of people, processes, as well as products and services in favor of the needs of humanity. The objective of this work is to analyze specifically the relation of the main projects of the re-arming of the Brazilian Armed Forces, as well as to clarify the role of the technological development of the defense, in the search of the state-of-the-art technology through the national industry. The replenishment plans and the organizations and companies involved, working cooperatively, can develop innovations for the country as well as products used in the day to day of the citizen. The work seeks to identify some of the new cutting-edge technologies of national companies involved in the defense sector, with the incentive to technological development, and the reduction of external dependence on equipment and products. The research will be carried out with the theme of the importance of the Armed Forces for the technological development of Brazil through its reequipment in the period from 2008 to 2018. The research will use a bibliographical survey between the re-engineering projects and some of the main industries of the defense sector, for which we chose the deductive method. The work will be used as a Questionnaire applied to specialists in the Defense sector, authorities who have held positions in the NDT processes, or who work in the military area.
The importance of the armed forces for development technological development in Brazil (2008-2018)
Keywords: Defesa; Inovação; Segurança Nacional; Tecnologia; Defense; Innovation; National Security; Technology; CNPQ::CIENCIAS SOCIAIS APLICADAS